Influence of the flow rate and the tank stratification degree on the performances of a solar flat-plate collector - Cristofari, C.; Notton, G.; Poggi, P.; Louche, A.
Using a thermal model of finite differences, the performances of a solar flat-plate thermal collector wholly manufactured in a copolymer material is studied in low flow conditions. The influences of the flow rate and the stratification of the tank are analysed. Thermal performances, productivity and efficiency of such a solar system (collector with surface of 2 m2 and a storage tank of 150 litres)are presented for a Mediterranean site. Such a system presents a yearly mean efficiency of about 55.5
Keywords: SOLAR FLAT-PLATE COLLECTOR; COPOLYMER; STRATIFIED TANK; FLOW RATE; MODELING; PERFORMANCE